Strategi Pengembangan Edutourism Kebun Kopi Terhadap Kesejahteraan Masyarakat Sembalun Sajang (Studi Kasus Pada Kelompok Tani Bumi Lestari) - Afwan Abrory; I Made Murdana (Pusat Penelitian Dan Pengabdian Masyarakat STIEPARI Semarang, 2023)
Sembalun coffee plantations used to be very extensive coffee plantations, in which the livelihoods of the Sembalun people were coffee grown during the Dutch Colonialization era as the main producer of coffee in Lombok. The general research objective is to analyze edutourism management strategies for coffee plantations for the welfare of the people of Sembalun Sajang. The method used is descriptive qualitative method by means of interviews and field observations. Based on the results of the research, it shows that in the conservation aspect, the Bumi Lestari Farmers Group has carried out several missions for the development of the Edutourism area in Sembalun Sajang Village, such as preserving nature. On the economic aspect, it has provided economic benefits for area managers, tour organizers and the local community.In the aspect of the active role of the community, the result is that the surrounding community has contributed to the development of science by collaborating with government and private parties so that everything can run well in accordance with prevailing trends . And in the tourism aspect, special attention is needed from the local office to improve facilities and provide clear access to information for potential tourists so they want to come for a tour of this educational area.